PROLONGED EXPOSURE TO DIFFERENT TYPES OF ENERGY RESTRICTED CALCIUM DIET MODULATES THE INFLAMMATORY AND OXIDATIVE STRESS RESPONSE IN HEALTHY MALE RATS: calcium diet, inflammation and oxidative stress - SANDEEP DAS; DIPAYAN CHOUDHURI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Emerging evidence established the role of dietary calcium in the modulation of obesity. Obesity is known to induce inflammatory and oxidative stress in adipocytes resulting in several metabolic complications. In the present study, we evaluated the role of low and high calcium diet on systemic inflammatory response and oxidative stress markers in both plasma and hepatic tissues in male rats. Methods: A total of 30 male rats were divided into three groups and fed with control, low calcium (0.25%), and high calcium (1.0%) diet for 3 months. All the diets were isocaloric in nature. At the end of the treatment, all rats were sacrificed, followed by collection of blood and hepatic tissue for inflammatory, oxidative, antioxidant, and histological study. Results: Rats fed with a low calcium diet showed a significant increase in the body weight gain, liver mass, plasma inflammatory markers C-reactive protein, interleukin-6, and tumor necrosis factor-alpha. Low calcium diet significantly increased the lipid peroxidation and protein carbonylation and decreased the superoxide dismutase and glutathione peroxidase activities in both plasma and liver. High calcium diet, on the other hand, showed the reversed effect. Conclusion: Low calcium in the diet, along with obesity, increases the systemic inflammatory response, which in turn increases oxidative stress both in blood and hepatic tissues. This might be associated with obesity-induced hepatic disorder. High calcium in diet attenuates this effect.